Price volatility and quinoa consumption among smallholder producers in the Andes (Scientia Agropecuaria, 2020)
The recent attention to quinoa as a nutritious food is changing the way the crop is produced and consumed by smallholders in the Andes. Price spikes and increased volatility in international quinoa prices have created a concern about quinoa consumption among Andean farm-households. The farm-household theory was used to investigate how food price changes affect household consumption and production decisions. Theoretical predictions were applied to original survey data from a quinoa-producing region of Peru. Findings suggest that the global quinoa hype and consequent price spikes did not adversely affect the consumption of this nutritious food among quinoa producers.